Cooperation, but No Reciprocity: Individual Strategies in the Repeated Prisoner’s Dilemma - Breitmoser, Yves (American Economic Review, 2015)
In the repeated prisoner's dilemma, predictions are notoriously difficult. Recently, however, Blonski, Ockenfels, and Spagnolo (2011)—henceforth, BOS—showed that experimental subjects predictably cooperate when the discount factor exceeds a particular threshold. I analyze individual strategies in four recent experiments to examine whether strategies are predictable, too. Behavior is well summarized by “Semi-Grim” strategies: cooperate after mutual cooperation, defect after mutual defection, randomize otherwise. This holds both in aggregate and individually, and it explains the BOS-threshold: Semi-Grim equilibria appear as the discount factor crosses this threshold, and then, subjects start cooperating in round 1 and switch to Semi-Grim in continuation play. (JEL C72, C73, C92, D12)